Virtual Learning During the COVID-19 Pandemic: A Bibliometric Review and Future Research Agenda - Bilal; Hysa E; Akbar A; Yasmin F; Rahman AU; Li S (Dove Medical Press, 2022)
Bilal,1 Eglantina Hysa,2 Ahsan Akbar,3 Fakhra Yasmin,4 Atteeq ur Rahman,5 Shengbing Li4,6 1School of Accounting, Hubei University of Economics, Wuhan, People's Republic of China; 2Department of Economics, Epoka University, Tirana, Albania; 3International Business School, Guangzhou City University of Technology, Guangzhou, 510080, People's Republic of China; 4School of Education, South China Normal University, Guangzhou, 510631, People's Republic of China; 5Department of Management Sciences, University of Gujrat, Gujrat, Pakistan; 6Center of Cross Border Education, School of International Business, South China Normal University, Guangzhou, 510631, People's Republic of ChinaCorrespondence: Ahsan Akbar, Tel +86 13802400964, Email akbar@gcu.edu.cnAbstract: Virtual learning has emerged as a powerful platform for students and academicians in the "new normal" owing to the availability of advanced technological tools and platforms. Recently, considerable literature has grown up around the role of digital and remote technologies in learning and teaching during the ongoing COVID-19 pandemic. However, the research evidence on this topic is still fragmented, requiring a synthesis of this rapidly growing literature. This study aims to assess the key research trends in virtual learning during the COVID-19 pandemic through a bibliometric analysis of 1595 studies from 589 journals during 2020- 21. Our study highlights the influential aspects, such as the most contributing countries, journals, authors, and keywords in this research field. We identified the following four main research trends: 1) challenges in online learning and blended learning strategies; 2) student-centered, collaborative learning, and curriculum design; 3) home-based laboratory learning; and 4) teachers' professional competence and interdisciplinary learning. We conclude this research by discussing the implications for regulators and educational institutions, and directions for future research.Keywords: COVID-19 pandemic, educational technologies, virtual learning, online learning, remote learning, students, teachers